Enhancing Elementary Students’ Procedural Writing through a Hybrid Approach of Problem-Based Learning and Differentiated Instruction - Yulia Yulia; Gusti Yarmi; Linda Zakiah (EduBase : Journal of Basic Education, 2026)
Objective: This study aims to examine the effectiveness of a hybrid instructional model integrating Problem-Based Learning (PBL) and Differentiated Instruction (DI) to improve procedural writing skills among fifth-grade elementary students in Indonesia. Novelty: The study introduces a combined PBL–DI framework within a Classroom Action Research (CAR) design, specifically applied to genre-based procedural writing instruction in diverse elementary classrooms. Methods: The research employed a two-cycle Classroom Action Research (CAR) design involving 31 students. Learners engaged in real-world writing tasks tailored to their readiness levels, interests, and learning profiles. Data were collected through writing assessments, observation sheets, reflection journals, field notes, and interviews, and analyzed using descriptive statistics and thematic analysis. Results: Student writing mastery improved significantly from 32% in the pre-action stage to 84% at the end of Cycle II. Qualitative findings indicated increased engagement, greater autonomy in writing, and enhanced self-efficacy. Contextual problem-solving tasks, scaffolded support, and iterative teacher reflection contributed to both cognitive and affective development. Conclusions: Integrating PBL and DI provides an effective, student-centered framework for enhancing procedural writing skills and offers a promising approach for genre-based writing instruction in diverse elementary school settings.